If women rose rooted eaudiobook The journey to authenticity and belonging. - Blackie, Sharon (Tantor Audio, 2017)
This is the second edition of a uniquely empowering, international word-of-mouth bestseller about wild landscapes, female mythology, and the challenges facing modern women. It is a book for any woman who has ever lost her way and who sees a wasteland at the heart of modern existence and longs to live a more authentic, rooted life once again.